Impact of Discharge to Rehabilitation on Postdischarge Morbidity Following Multilevel Posterior Lumbar Fusion. Issue 1 (February 2022) - Song, Junho; Katz, Austen D.; Perfetti, Dean; Job, Alan; Morris, Matthew; Goldstein, Jeffrey; Virk, Sohrab; Silber, Jeff; Essig, David
Abstract : Study Design: This was a retrospective cohort study. Objective: The objective of this study was to compare 30-day postdischarge morbidity for 3-or-more level (multilevel) posterior lumbar fusion in patients who were discharged to home versus rehabilitation. Summary of Background Data: Spine surgery has been increasingly performed in the elderly population, with many of these patients being discharged to rehabilitation and skilled nursing facilities. However, research evaluating the safety of nonhome discharge following spine surgery is limited. Materials and Methods: Patients who underwent multilevel posterior lumbar fusion from 2005 to 2018 were identified using the National Surgical Quality Improvement Program (NSQIP) database. Regression was utilized to compare primary outcomes between discharge disposition and to evaluate for predictors thereof. Results: We identified 5276 patients. Unadjusted analysis revealed that patients who were discharged to rehabilitation had greater postdischarge morbidity (5.6% vs. 2.6%). After adjusting for baseline differences, discharge to rehabilitation no longer predicted postdischarge morbidity [odds ratio (OR)=1.409, confidence interval: 0.918–2.161, P =0.117]. Multivariate analysis also revealed that age ( P =0.026, OR=1.023), disseminated cancer ( P =0.037, OR=6.699), and readmission ( P <0.001, OR=28.889) independently predicted postdischarge morbidity. Conclusions: Thirty days morbidity was statistically similar between patients who were discharged to home and rehabilitation. With appropriate patient selection, discharge to rehabilitation can potentially minimize 30-day postdischarge morbidity for more medically frail patients undergoing multilevel posterior lumbar fusion. These results are particularly important given an aging population, with a great portion of elderly patients who may benefit from postacute care facility discharge following spine surgery.